2017
DOI: 10.1212/wnl.0000000000003841
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and accuracy of teleconcussion for acute evaluation of suspected concussion

Abstract: Objective: To assess the feasibility and accuracy of telemedical concussion evaluations (teleconcussion) for real-time athletic sideline assessment of concussion, as such assessment may address the gap in access some populations of athletes have to providers with expertise in concussion evaluation.Methods: A cohort of 11 consecutive male collegiate football players with suspected concussion was assessed using Standardized Assessment of Concussion (SAC), King-Devick test (K-D), and modified Balance Error Scorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 9 publications
0
40
0
Order By: Relevance
“…The diagnosis of acute concussion requires a physician to reliably exclude more serious forms of TBI, as well as structural injury to the cervical spine, which can only be accomplished through a careful history, focused physical examination and the evidence-based use of diagnostic imaging [43]. Although some authors have demonstrated the feasibility and reliability of using abbreviated concussion screening tools, such as the Sport Concussion Assessment Tool (SCAT) and King-Devick Test via telemedicine videoconferencing [35,36], several essential aspects of the neurological examination including testing of motor and sensory functioning, tone, reflexes and fundoscopy can not be performed unless another trained clinician is available to conduct these tests and present the findings to the remote consulting physician [44,45]. Subtle signs appreciated during objective assessment of oculomotor, vestibular and cervical spine function can be helpful in guiding clinical decisions regarding the need for diagnostic imaging and targeted rehabilitation but are also challenging or impossible to elicit during telemedicine consultations [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of acute concussion requires a physician to reliably exclude more serious forms of TBI, as well as structural injury to the cervical spine, which can only be accomplished through a careful history, focused physical examination and the evidence-based use of diagnostic imaging [43]. Although some authors have demonstrated the feasibility and reliability of using abbreviated concussion screening tools, such as the Sport Concussion Assessment Tool (SCAT) and King-Devick Test via telemedicine videoconferencing [35,36], several essential aspects of the neurological examination including testing of motor and sensory functioning, tone, reflexes and fundoscopy can not be performed unless another trained clinician is available to conduct these tests and present the findings to the remote consulting physician [44,45]. Subtle signs appreciated during objective assessment of oculomotor, vestibular and cervical spine function can be helpful in guiding clinical decisions regarding the need for diagnostic imaging and targeted rehabilitation but are also challenging or impossible to elicit during telemedicine consultations [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has demonstrated the feasibility of using telemedicine to assist with the clinical care of patients with a wide spectrum of neurological conditions including stroke [16,21,22], headache [23][24][25], multiple sclerosis [26], mental health disorders [27,28], epilepsy [29,30] and neurodegenerative diseases [31][32][33][34]. Although preliminary studies have suggested that telemedicine may be helpful in providing sideline and inoffice care to patients with concussion [35,36], there have been no studies that have examined the use of this technology to provide clinical care of paediatric concussion patients living in remote and medically underserviced communities in northern Canada.…”
mentioning
confidence: 99%
“…67 Telehealth for mental healthcare has not been systematically studied in athletes, but this method of care delivery is feasible for athletes with other medical needs. [68][69][70] For athletes in some countries, remote provision of mental healthcare has necessitated changes in licensure rules. 17 For example, in the USA, during non-pandemic times, a physician must be licensed in the state where the patient is physically located, 17 and most physicians are only licensed in a single state.…”
Section: Virtual Versus In-person Carementioning
confidence: 99%
“…There is limited research on the feasibility of assessing individuals with traumatic brain injury (TBI) using telephone or virtual methods. Preliminary work has been conducted in the area of sports medicine evaluating the potential for "teleconcussion" assessment and care (Vargas et al, 2012(Vargas et al, , 2017. However, this method requires a remote assessment centre and trained staff to complete cognitive, balance, and brief neurological examinations before consulting via videoconference with a neurologist.…”
Section: Traumatic Brain Injurymentioning
confidence: 99%